1999
DOI: 10.1162/105474699566530
|View full text |Cite
|
Sign up to set email alerts
|

Use of Virtual Environments for Acquiring Configurational Knowledge about Specific Real-World Spaces: I. Preliminary Experiment

Abstract: A relatively simple architectural space was modeled and used to compare the effects of spatial training in simulations versus training in the real world. Thirty-five subjects were trained in one of the following conditions: real world (RW), virtual environment (VE), nonimmersive virtual environment (NVE), and model (Mod). The VE condition made use of a head-mounted display to view the simulated environment, while the NVE condition used a desktop monitor. In the Mod condition, the subject viewed and could manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 24 publications
0
38
0
2
Order By: Relevance
“…Instead of confronting people with fixed, controlled, prearranged conditions, VE compel them to move in order to discover the affordances latent in the environment (Mantovani 1996b). Recent research provides evidence of the fact that experience in a VE can stimulate acquisition of configurational knowledge about specific real-world spaces (Koch et al 1999). This scientific result encouraged us to develop a virtual library (VL) as a tool to study the suitability of VE for safety training in large public spaces.…”
Section: From Simulated To Everyday Situationsmentioning
confidence: 99%
“…Instead of confronting people with fixed, controlled, prearranged conditions, VE compel them to move in order to discover the affordances latent in the environment (Mantovani 1996b). Recent research provides evidence of the fact that experience in a VE can stimulate acquisition of configurational knowledge about specific real-world spaces (Koch et al 1999). This scientific result encouraged us to develop a virtual library (VL) as a tool to study the suitability of VE for safety training in large public spaces.…”
Section: From Simulated To Everyday Situationsmentioning
confidence: 99%
“…They attributed these inconsistencies to differences in the VE systems, environments, and training methods used. Likewise, as reviewed by Koh, Wiegand, Garnett, Durlach, and Shinn-Cunningham (1999), comparisons of map and VE training have produced mixed results in terms of real-world performance, with map training better in some experiments, and VE training better than others.…”
Section: Discussionmentioning
confidence: 99%
“…The activities to be carried out in the present workshop are based on previous research on spatial orientation with navigation in immersive virtual environments (Witmer et al, 1995;Waller et al, 1998;Koh et al, 2000;Darken and Peterson, 2001). …”
Section: Methodsmentioning
confidence: 99%
“…Waller (1999) states that the estimation of the distance during a process of immersion in a virtual world is similar to that obtained in a real-world environment. Moreover, Witmer et al (1995), Bliss et al (1997), and Koh et al (2000) concluded that, for the acquisition of spatial knowledge, immersive VE environments are as effective as real-world environments. Spatial knowledge acquisition depends on the fidelity of the environments, the interfaces to these systems and the methods of training.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%